Intracerebral estrogen provision increases cytogenesis and neurogenesis in the injured zebra finch brain - Walters, Bradley J. (2011)
To determine whether or not local, injury-induced aromatization and/orestrogen provision can affect cyto-or neuro-genesis following mechanical brain damage, two groups of adult male zebra finches sustained bilateral penetrating brain injuries. The first received contralateral injections of vehicle or the aromatase inhibitor fadrozole. The second group received contalateral injections of fadrozole, or fadrozole with 17β-estradiol. Subsequent to injury, birds were injected with the thymidine analog 5-Bromo-2′-deoxyuridine (BrdU). Two weeks following injury, the birds were perfused, and coronal sections were labeled using antibodies against BrdU and the neuronal proteins HuC/HuD. In a double blind fashion, BrdU positive cells and BrdU/Hu double-labeled cells in the subventricular zone (SVZ) and at the injury site (INJ) were imaged and sampled. The average numbers of cells per image were compared across brain regions and treatments using repeated measures ANOVAs and, where applicable, post-hoc, pairwise comparisons. Fadrozole administration had no detectable effect on cytogenesis or neurogenesis, however, fadrozole coupled with estradiol significantly increased both measures. The dorsal SVZ had the greatest proportion of new cells that differentiated into neurons, though the highest numbers of BrdU labeled and BrdU, Hu double-labeled cells were detected at the injury site. In the adult zebra finch brain, local estradiol provision can increase cytogenesis and neurogenesis, however, whether or not endogenous glial aromatization is sufficient to similarly affect these processes remains to be seen.